Pemodelan Volatilitas Return Saham: Studi Kasus Pasar Saham Asia - Sari, Linda Karlina; Achsani, Noer Azham; Sartono, Bagus (UI Scholars Hub, 2017)
Volatility is one of the interesting phenomenon in financial market; the reason is because of its effect to the existence of global financial market. The existence of volatility closely related to the risk in stock model. This research aims to determine the right model in modeling stock return volatility taken from four Asian countries with symmetric and various asymmetric model of GARCH. The result from fitting the right model for all of four stock markets showed that asymmetric model of GARCH showing a better estimation in portraying stock return volatility. Moreover, the model can reveal the existence of asymmetric effects on those four stock markets.